2019
DOI: 10.4103/ijd.ijd_579_18
|View full text |Cite
|
Sign up to set email alerts
|

Changing trend of superficial mycoses with increasing nondermatophyte mold infection: A clinicomycological study at a tertiary referral center in Assam

Abstract: Background: Superficial mycosis is the commonest infections affecting human globally. Though they do not cause mortality, their clinical significance lies in their morbidity, recurrence, and cosmetic disfigurement, thus creating a major public health problem. The infections are more prevalent in the tropical regions. The etiological agents are also seen to vary with time and geographical location. Aim: This study was carried out to find out the trend of superficial myco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 10 publications
1
18
1
Order By: Relevance
“…14 With regard to superficial dermatophytic infections, prevalence is found to be higher in younger population especially infections in the groin. 15 Prevalence of oral findings overall was low in our study with only 23.43% of women having complaints. Most of the women complained of a nonspecific oral discomfort without presence of any lesions.…”
Section: Discussioncontrasting
confidence: 60%
“…14 With regard to superficial dermatophytic infections, prevalence is found to be higher in younger population especially infections in the groin. 15 Prevalence of oral findings overall was low in our study with only 23.43% of women having complaints. Most of the women complained of a nonspecific oral discomfort without presence of any lesions.…”
Section: Discussioncontrasting
confidence: 60%
“…However, in the present epidemic, these boundaries are getting blurred with the rising incidence of dermatophytosis in women and children [Table 2]. 7,[12][13][14][15][18][19][20][21][22][23][24][25] It is clear that the male:female ratio is < 2 in all the studies published in the last 3-4 years [12][13][14][18][19][20] in contrast to earlier studies where the ratio was 3-5, indicating a rising prevalence in women. 24,25 Recent studies have even shown the reversal of the men:women ratio.…”
Section: Age and Sexmentioning
confidence: 99%
“…4 Moreover, a probability that the zoophilic Trichophyton mentagrophytes has acclimatised itself and has undergone anthropization leading to easy transmission among humans has been suggested. 4 In the past decade, and especially from the beginning of 2012, the reported prevalence of Trichophyton mentagrophytes has not only increased, 6,7,10,12,18,22,26,30 but it has even replaced Trichophyton rubrum in a few studies[Table 4]. [9][10][11]24,26 The most recent studies have found Trichophyton mentagrophytes in more than 90% of their dermatophyte isolates.…”
Section: Causative Organismmentioning
confidence: 99%
“…Superficial fungal infections of the nail (tinea unguium or onychomycosis) and skin (eg, tinea pedis) are most commonly caused by dermatophytes of the genus Trichophyton, accounting for 50% to 90% of such infections [1][2][3]. Trichophyton rubrum is the most common causative anthropophilic species (~90% of onychomycosis), followed by Trichophyton mentagrophytes (~8%) [4], while Trichophyton interdigitale alone comprises 15% of tinea pedis infections [5].…”
Section: Introductionmentioning
confidence: 99%